Interest in Continuing To Higher Education Based on Learning Achievement (Study On Students of SMA Negeri Sekota Semarang), Thesis. Economic Education Study Program Graduate State University of Semarang - Irmaya, Heti; Rusdarti, Rusdarti; Setyadharma, Andryan (Universitas Negeri Semarang, 2020)
Along with the development of the era the role of education is very important in preparing quality human resources. So that the rapid change of times can be responded by educational products, therefore students need to pursue higher education to be able to improve their quality. The purpose of this study was to analyze the influence of family learning and socioeconomic motivation on the interest of continuing to college through learning achievement as a variable of mediation. The population in this study was 5930 students, with proportional cluster random sampling technique obtained sample size of 375 students. Data collection techniques using questionnaires and documentation. Data analysis using path analysis and sobel test. The results showed that there is a direct influence of learning motivation on the interest of continuing higher education 12.1% and the influence of total motivation to study on interest in college through learning achievement of 26.4%, there is a direct influence of socioeconomic family front on interest to college 17% and there is a total influence of socioeconomic family on interest to college through learning achievement of 31.8%. The total influence is greater than direct influence, so it is concluded that there is mediation between learning motivation and socioeconomic family as an independent variable on the interest of continuing to college. Sobel Test results stated that the coefficient of mediation is significant, so that learning achievement is proven to mediate the influence of learning motivation and socioeconomic family on interest in college. Based on the results of the study, it was concluded that there is a positive influence of learning motivation, socioeconomic status of the family, and learning achievement on the interest of continuing education to higher education in students of SMA Negeri Sekota Semarang both simultaneously and partially. The advice given in this study is expected that parents can improve their family's socioeconomic degree in order to facilitate their children's education and students have a better motivation to learn ahead and have an impact on increased learning achievement so that students' interest in higher education will be stronger.